Hiring of Foreigners in Mozambique - Regulatory Regimes and Practices - JICA (Agency for Promotion of Investment and Exports (APIEX), 2019)
The laws and regulations for hiring foreign nationals have been enacted with the aim of protecting the national workforce, ensuring the availability of jobs for them, while limiting employment of foreigners to those positions with levels of technical and professional skills and qualifications which are either nonexistent or insufficient in the country. Historically, the main instrument used by the Mozambican Government to achieve foreign investment promotion balanced with national employment, was the hiring of foreign employees through the quota mechanism, which is still in use at present. In the present context, it is fundamental that the regime of hiring foreign labour allows for certain flexibility but at the same time does not compromise the structural principle of protecting the local labour force. This document is prepared to provide the current regulatory framework for hiring of foreign nationals, as a reference mainly for foreign investors considering employing foreigners in their projects in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego

Rules of the Game: An Introduction to the Standards-Related Work of the International Labour Organization - International Labour Organization (International Labour Organization, 2019)
The Rules of the Game: An introduction to the standards-related work of the ILO provides a brief presentation of the ILO’s standards policy with a view to facilitating understanding and ownership by the ILO’s traditional constituents, as well as the United Nations system, non-specialists and the broader public. In its first section, the publication recalls the underlying reasons for and utility of the ILO’s standards-related action at both the national level and in the current context of globalization. The content of international labour standards is then presented thematically in the second section. The third section consists of a description of the supervisory mechanisms of the application of international labour standards by ILO member States. The updating of this reference work, which was first published in 2005 and the most recent edition of which is dated 2014, bears witness to the dynamic nature of the ILO’s standards policy. The new 2019 edition, which coincides with the ILO’s centenary, describes recent developments, including the new instruments adopted, the launch of the Standards Centenary Initiative, which is intended to strengthen the supervisory system, and the establishment of the Standards Review Mechanism. It also places in perspective the essential contribution of international labour standards to the 2030 Sustainable Development Agenda adopted by the Member States of the United Nations in 2015, and the more general reflection on the Future of Work. This edition, prepared by Eric Gravel, of the International Labour Standards Department, contributes to promoting the Organization’s standards-related action and disseminating more broadly information on its standards-related mandate.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; employment / emprego